Attitudes of senior high school students toward vocational education in selected schools in Quezon City - Sengsai, Dhanee 1944- (1974)
The attitude of senior high school students in selected high schools in Quezon City toward vocational education was determined in this study. The study also analyzed the relationship between students' attitude and the following variables: sex, age, parents' occupation, parents' educational attainment and the number of siblings in the family. The implications of these findings on educational administration were then investigated.
Thesis (M.Ed.)--University of the Philippines
Keywords: Vocational education -- Philippines; Students -- Philippines